Susceptibility analysis of Arcobacter isolated from fresh cheeses from municipal markets to fluoroquinolones in Guaranda City, Ecuador. - Bayas Morejón , Favian (2022)
https://cjes.guilan.ac.ir/article_5584_43b5160f965916ef2f7f1be9a0fd38a6.pdf